IMPROVING TREATMENT OPTIONS IN POLYCYTHEMIA VERA: FROM INTERFERON TO NEW AGENTS - Can Özlü (Hematology, Transfusion and Cell Therapy)
Polycythemia Vera (PV) is a chronic myeloproliferative neoplasm characterized by the overproduction of red blood cells, often accompanied by increased white blood cells and platelets. The disease is primarily driven by mutations in the Janus kinase 2 (JAK2) gene, specifically the JAK2 V617F mutation, which is present in approximately 95% of patients. The clinical presentation of PV includes a range of symptoms that significantly impact the quality of life (QoL) of affected individuals. Common symptoms include fatigue, pruritus, headaches, and visual disturbances, which are often attributed to the hyper viscosity of the blood resulting from increased red blood cell mass. The diagnosis of PV is based on the World Health Organization (WHO) criteria, which include elevated hemoglobin or hematocrit levels, the presence of the JAK2 mutation, and evidence of bone marrow hypercellularity. Diagnostic challenges may arise due to overlapping features with other myeloproliferative neoplasms, necessitating comprehensive blood evaluations and sometimes bone marrow biopsies. The disease is associated with a significant risk of thrombotic events, including stroke and myocardial infarction, which can occur in up to 26% of patients. Furthermore, the risk of transformation to more severe forms of hematological malignancies, such as acute myeloid leukemia (AML) or myelofibrosis, is notable, with studies indicating a transformation rate of approximately 10% over a 20-year period. Management of PV focuses on reducing the risk of thrombotic complications and alleviating symptoms. Phlebotomy is often the first-line treatment to reduce hematocrit levels, particularly in patients with high thrombotic risk. In cases where phlebotomy is insufficient or not tolerated, cytoreductive therapies, such as hydroxyurea, are commonly employed. However, approximately 25% of patients may experience inadequate responses or unacceptable side effects from hydroxyurea, necessitating alternative treatments. Ruxolitinib, a JAK2 inhibitor, has emerged as a promising option for patients who do not respond adequately to conventional therapies, demonstrating efficacy in reducing splenomegaly and symptom burden. In conclusion, PV is a complex hematological disorder with significant clinical implications. Early diagnosis and appropriate management are crucial to mitigate the risks associated with the disease. Ongoing research into novel therapeutic agents and treatment strategies continues to enhance our understanding and management of this condition, ultimately aiming to improve patient outcomes and QoL.